Leadership Of The Head Of Culture, Tourism, Youth And Sports Department In Development Of Nyi Mas Gandasari Site Tourist Destination In Depok District, Cirebon Regency - Nurudin Siraj (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
The research that the author has done is about the leadership of the Head of Culture and Tourism Department in the Development of the Nyi Mas Gandasari Site Tourist Destination in Depok District, Cirebon Regency. Based on the observations made by the author, there are symptoms of problems in the development of tourist destinations for the Nyi Mas Gandasari Site in Depok District, Cirebon Regency, that is the less optimal development of the Nyi Mas Gandasari Site carried out by the Cirebon Regency Culture and Tourism Department. Based on these problems, there is an identification of the problem, such as How the Role of the Culture and Tourist Department Leadership in the development of the Nyi Mas Gandasari Site Tourism Destination in Depok District, Cirebon Regency, what are the obstacles to the role of the Culture and Tourism Department Leadership in the Development of the Nyi Mas Gandasari Site Tourist Destination in Depok District Cirebon Regency and what efforts are made to overcome obstacles in the Leadership of the Head of the Culture and Tourism Department in the development of the Nyi Mas Gandasari Site Tourist Destination in Depok District, Cirebon Regency. The purpose of the research that the authors do is to find out how the leadership of the Head of the Culture and Tourism Department in the development of the Nyi Mas Gandasari Site Tourist Destination in Depok District, Cirebon Regency and what factors influence the development of the Nyi Mas Gandasari Site Tourist Destination in Depok District, Cirebon Regency. The research method used is a qualitative method which is descriptive in nature. The research that the author does is to explore, find and explain the leadership of the Head of the Culture and Tourism Department in developing the Nyi Mas Gandasari Site Tourist Destination in Depok District, Cirebon Regency. The results of the leadership research of the Head of the Culture and Tourism Department in the development of the Nyi Mas Gandasari Site Tourist Destination in Depok District, Cirebon Regency, are that the development of cultural heritage in Cirebon Regency is not yet optimal and does not have a legal umbrella related to the preservation of cultural heritage in Cirebon Regency.